Marketing Verde y Comportamiento del Consumidor de una empresa biotecnológica - Panta Merino, Monica Esther; Alcántara Moncada, Ariana Malen; Fernández Ruiz, Marjorie Alexandra; Valderrama Puscan, Marlon Walter (LACCEI, 2025)
This research aligns with Sustainable Development Goal 12: Responsible consumption and production, by analyzing the relationship between green marketing and consumer behavior in a biotechnology company located in Ica, Peru. The objective was to determine how the dimensions of ecological marketing (product, price, place, and promotion) influence customer purchasing decisions. The study adopted a quantitative, correlational, basic, and non-experimental design, applying surveys to 73 clients of the company through a census approach. The results revealed a strong positive correlation (Rho = 0.693; p < 0.01) between green marketing and consumer behavior. The regression model explained 60.6% of the variability in consumer behavior, with green promotion (β = 0.455) and green pricing (β = 0.381) emerging as significant predictors. It is concluded that green marketing practices, particularly those focused on communication and perceived ecological value, significantly influence purchasing behavior. The company is advised to strengthen these strategies to consolidate a sustainable and competitive market position